2012
DOI: 10.1007/s11664-012-1976-y
|View full text |Cite
|
Sign up to set email alerts
|

Disabling of Nanoparticle Effects at Increased Temperature in Nanocomposite Solders

Abstract: The use of nanoparticles to control grain size and mechanical properties of solder alloys at high homologous temperature is explored. It is found that silica nanoparticles in the 100 nm range coated with 2 nm to 3 nm of gold can be dispersed within solders during the normal reflow soldering process, and that these particles are effective in hardening the solder and restricting dynamic grain growth during compression testing at low homologous temperature. As the homologous temperature increases towards 0.75, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 23 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…In [55], Mokhtari et al studied the effect of nanoparticle size and temperature in nanocomposite solders; they noted that also the stress of the pinning effect of nanoparticles on the grains was reduced because thermal fluctuations increased. They concluded that the number of nanoparticles participating in pinning grain boundaries is reduced to the effective fraction of nanoparticles that interact with the grain structures f eff : where Q is an activation energy R is the molar gas constant, and T is the working temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In [55], Mokhtari et al studied the effect of nanoparticle size and temperature in nanocomposite solders; they noted that also the stress of the pinning effect of nanoparticles on the grains was reduced because thermal fluctuations increased. They concluded that the number of nanoparticles participating in pinning grain boundaries is reduced to the effective fraction of nanoparticles that interact with the grain structures f eff : where Q is an activation energy R is the molar gas constant, and T is the working temperature.…”
Section: Resultsmentioning
confidence: 99%
“…A weak electrostatic force between TiO 2 nanoparticle and metallic SAC alloys that encourages the TiO 2 nanoparticle expelled from the solder matrix during the soaking stage of the reflow process. Thermal loads above 150°C imposed on the solder paste during the soaking phase (Lee, 2002; Mokhtari et al , 2012) activate the flux. Hence, the TiO 2 nanoparticles were upwardly displaced because of the weak intermolecular forces.…”
Section: Resultsmentioning
confidence: 99%
“…The large amount of NiO nanoparticles were easily expelled from the solder matrix during the soaking stage because of a weak electrostatic force of attraction with metallic SAC alloys. When the nanocomposite solder paste received thermal loads above 150°C during the soaking phase (Lee, 2002;Mokhtari et al, 2012), the flux was activated and the NiO nanoparticles were upwardly displaced because of weak intermolecular forces. Both SAC alloys and NiO nanoparticles in the solder matrix are by strong metallic bonds and covalent bonds, respectively.…”
Section: Figure 15 Reflowed Pcbmentioning
confidence: 99%